Mentoring the Development of Jaran Kepang Art Creations by the Satrio Putro Arema Art Group in Cemorokandang Village, Kedungkandang District, Malang City: Pendampingan Pengembangan Kreasi Seni Jaran Kepang Kelompok Seni Satrio Putro Arema di Kelurahan Cemorokandang Kecamatan Kedungkandang Kota Malang - Gatut Rubiono; M. Agung Setiabudi; Donny Setiawan (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Satrio Putro Arema is an arts group which developing the Jaran Kepang dance art. This development is hampered by the need for equipment, which is still being borrowed or rented. This community service activity aims to provide support for the development of the Jaran Kepang art creations of the Satrio Putro Arema arts group in Cemorokandang Village, Kedungkandang District, Malang City. The activity involved initial observation, equipment procurement, dance practice, and performances. The results of the activity showed an improvement in the quality of the partners' performances.